The Salience of Saintliness in Islam: A Sufi Perspective - Wael Hegazy (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2021)
While materialism largely failed in achieving humanity’s essential goal of attaining happiness in life, as it intensified people’s attachment to the material world, spirituality represents an alternative way towards accomplishing ultimate joy. Multiple approaches have brought the value of spirituality. Classical saintly experience and practice have played a significant role in Islamic spirituality and became in its various forms integrated into social, political, and intellectual life. This paper discusses the ascetic practices of Sufis in approaching the ultimate spiritual goal of inner purification. While classical Sufism’s disciplinary methods have varied significantly across time and place, in many cases, these practices revolve around obedience and asceticism. It then discusses the unique attributes Sufi saints are characterized that speak to the existence of more profound dimensions of reality such as Wilāya and Baraka and their impact on social life.